Assessment of filtered cameras for quantitative 2D analysis of divertor conditions during detachment in JET L-mode plasmas. (1st July 2021) - Karhunen, J; Lomanowski, B; Solokha, V; Aleiferis, S; Carvalho, P; Groth, M; Lawson, K D; Meigs, A G; Shaw, A
Abstract: Estimates for 2D distributions of electron temperature, T e, electron density, n e, and atomic deuterium density, n 0, in the JET divertor volume have been inferred from deuterium Balmer line intensity ratios obtained from tomographic reconstructions of divertor camera measurements. This enables also investigation of ionization, S i o n, and recombination, S r e c, rates. The analysis shows a decrease of T e to 0.5–1.0 e V throughout the outer divertor during detachment in low-confinement (L-mode) plasmas. Simultaneously, the high- n e region and the n 0 distribution in the outer divertor are observed to elongate and shift from the outer strike point towards the X-point. The observations are in qualitative agreement and follow the same sequence with modelling predictions of EDGE2D-EIRENE simulations of a density scan. While the method was found to provide good representation of the evolution of volumetric recombination during detachment, in agreement with the simulations, the movement of the ionization front upstream could not be followed due to lack of spatial overlap between the ionization region and the necessary emission distributions. Consequently, the representation of the ionization conditions and the particle balance in the detached outer divertor are compromised.